On upper and lower weakly $τ^\starβ(σ_1,σ_2)$-continuous multifunctions (European Journal of Pure and Applied Mathematics, 2025)
A new class of continuous multifunctions between an ideal topological space and a bitopological space,called upper (lower) weakly $τ^\starβ(σ_1,σ_2)$-continuous multifunctions, has been defined and studied. Furthermore, several characterizations and some properties concerning upper weakly$τ^\starβ(σ_1,σ_2)$-continuous multifunctions and lower weakly $τ^\starβ(σ_1,σ_2)$-continuous multifunctions are discussed.
Keywords: upper weakly $τ^\starβ(σ_1,σ_2)$-continuous multifunction; lower weakly $τ^\starβ(σ_1,σ_2)$-continuous multifunction